Analysis Effect of Role-Playing Method Assisted by Audio Visual Media on Speaking Skills in Indonesian Language Learning for Elementary School Students - Rohadatul Aisy; Abdul Rahman Jupri (Jurnal Paedagogy, 2022)
This study aims to analyze the effect of the role-playing method assisted by audio-visual media on speaking skills in Indonesian language learning at SDN Cibuntu 01. The method used in this research is quantitative as a kind of quasi-experimental research design with One Group Pretest-Posttest Design which only involves one group for initial treatment, treatment, and end of treatment. The research instrument was a speaking skill test consisting of 5 rules with 25 descriptors to measure students' speaking ability which experts had approved. The data analysis technique used in this study was the normality test using the Liliefors test and the homogeneity test using the Fisher test. Then, the hypothesis was tested using the t-test. Data processing was done with the help of SPSS 25 software with a significant level of 5% or =0.05. Based on the results of this study, it was obtained that the tcount > ttable was 2.802 > 1.701. As these results show, H₀ is rejected and H₁ is recognized. Therefore, the role-playing method assisted by audio-visual media affects speaking skills in Indonesian language learning for grade 3 students at SDN Cibuntu 01. The implication for learning Indonesian is that selecting the proper method can affect students' speaking skills. There are differences in speaking skills between Indonesian language learning and those taught before and after using the role-playing method with the aid of audio-visual media. It is seen from the confidence in playing the character; the voice volume becomes louder, the body movements are more flexible, understanding the story content well, pronunciation and proper intonation.